Workload with Emergency Installation Nurse Work Stress - Suriyani Suriyani; Glendy Ariando Salomon; Richard Andreas Palilingan; Suprapto Suprapto (Jurnal Edukasi Ilmiah Kesehatan, 2023)
The state of the nurse's workload in the emergency department needs to be known for its quantity and quality. If the number of tasks is not proportional to the ability of both physical and expertise and the time available, it will be a source of stress. The study aimed to determine the workload with work stress in nurses in the emergency room. Quantitative research with a correlation descriptive approach, with a sample of 29 respondents using a daily log study measuring instrument. The statistics test results show a workload with a p-value of 0.000. It can be concluded that there is a relationship between workload and the work stress of nurses in the emergency room. Recommendations for nurses need effective and constructive self-management so that there is a high workload and nurse work stress can be effectively controlled to not impact the quality of service.